Left Ventricular Noncompaction and Congenital Heart Disease Increases the Risk of Congestive Heart Failure - Keiichi Hirono (Journal of Clinical Medicine, 2020)
Background: Left ventricular noncompaction (LVNC) is a hereditary cardiomyopathy that is associated with high morbidity and mortality rates. Recently, LVNC was classified into several phenotypes including congenital heart disease (CHD). However, although LVNC and CHD are frequently observed, the role and clinical significance of genetics in these cardiomyopathies has not been fully evaluated. Therefore, we aimed to evaluate the impact on the perioperative outcomes of children with concomitant LVNC and CHD using next-generation sequencing (NGS). Methods: From May 2000 to August 2018, 53 Japanese probands with LVNC (25 males and 28 females) were enrolled and we screened 182 cardiomyopathy-associated genes in these patients using NGS. Results: The age at diagnosis of the enrolled patients ranged from 0 to 14 years (median: 0.3 months). A total of 23 patients (43.4%) were diagnosed with heart failure, 14 with heart murmur (26.4%), and 6 with cyanosis (11.3%). During the observation period, 31 patients (58.5%) experienced heart failure and 13 (24.5%) developed arrhythmias such as ventricular tachycardia, supraventricular tachycardia, and atrioventricular block. Moreover, 29 patients (54.7%) had ventricular septal defects (VSDs), 17 (32.1%) had atrial septal defects, 10 had patent ductus arteriosus (PDA), and 7 (13.2%) had Ebstein’s anomaly and double outlet right ventricle. Among the included patients, 30 underwent surgery, 19 underwent biventricular repair, and 2 underwent pulmonary artery banding, bilateral pulmonary artery banding, and PDA ligation. Overall, 30 genetic variants were identified in 28 patients with LVNC and CHD. Eight variants were detected in MYH7 and two in TPM1. Echocardiography showed lower ejection fractions and more thickened trabeculations in the left ventricle in patients with LVNC and CHD than in age-matched patients with VSDs. During follow-up, 4 patients died and the condition of 8 worsened postoperatively. The multivariable proportional hazards model showed that heart failure, LV ejection fraction of < 24%, LV end-diastolic diameter z-score of > 8.56, and noncompacted-to-compacted ratio of the left ventricular apex of > 8.33 at the last visit were risk factors for survival. Conclusions: LVNC and CHD are frequently associated with genetic abnormalities. Knowledge of the association between CHD and LVNC is important for the awareness of clinical implications during the preoperative and postoperative periods to identify the populations who are at an increased risk of additional morbidity.